Optimization of hydropower reservoir operation based on hedging policy using Jaya algorithm - Chong K.L.; Lai S.H.; Ahmed A.N.; Wan Jaafar W.Z.; El-Shafie A. (Elsevier Ltd, 2023)
Ant colony optimization; Hydroelectric power; Hydroelectric power plants; Investments; Particle swarm optimization (PSO); Reservoirs (water); Stream flow; Water supply; Ant colony algorithms; Hydro-power generation; Hydropower reservoirs; Optimization algorithms; Particle swarm optimization algorithm; Reservoir performance; Streamflow generations; Uncertainty and variability; Genetic algorithms